2016
DOI: 10.1093/neuonc/now165
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive function varies by IDH1 genetic mutation status in patients with malignant glioma prior to surgical resection

Abstract: Background.Patients with malignant gliomas present with variation in neurocognitive function (NCF) not attributable to lesion size or location alone. A potential contributor is the rate at which tumors grow, or "lesion momentum." Isocitrate dehydrogenase 1 wild type (IDH1-WT) are more proliferative and aggressive than IDH1-mutant (IDH1-M) tumors. We hypothesized that patients with IDH1-WT would exhibit worse NCF than patients with IDH1-M tumors. Methods.Comprehensive NCF testing was completed in 119 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
109
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 34 publications
4
109
0
Order By: Relevance
“…The same group investigated cortical thickness covariation as a neural correlate of this difference, showing that thickness covariation patterns indeed differ between subgroups and associate with cognition (Kesler et al, ). This provides a first insight into possible mechanisms underlying IDH‐mutation‐related cognitive differences and also suggests that tumor growth rate might contribute to cognitive problems (Klein, ; Wefel et al, ). However, the observed group differences in covarying cortical thickness were not corrected for age or presence of epilepsy.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The same group investigated cortical thickness covariation as a neural correlate of this difference, showing that thickness covariation patterns indeed differ between subgroups and associate with cognition (Kesler et al, ). This provides a first insight into possible mechanisms underlying IDH‐mutation‐related cognitive differences and also suggests that tumor growth rate might contribute to cognitive problems (Klein, ; Wefel et al, ). However, the observed group differences in covarying cortical thickness were not corrected for age or presence of epilepsy.…”
Section: Discussionmentioning
confidence: 98%
“…Wefel and colleagues were the first to describe worse cognitive performance in patients with IDH‐wt glioma compared to patients with IDH‐mut glioma (Wefel et al, ). The same group investigated cortical thickness covariation as a neural correlate of this difference, showing that thickness covariation patterns indeed differ between subgroups and associate with cognition (Kesler et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also included education level considering its significant independent contribution, as a proxy of cognitive reserve [42], to cognitive outcome following cancer [43] and other neurologic conditions. Age and histology were not included in this or any other models given that these variables reflect the known etiologic and pathologic differences associated with IDH1 subtypes [7, 44]. …”
Section: Methodsmentioning
confidence: 99%
“…We recently demonstrated that patients with wild type malignant gliomas show greater cognitive dysfunction compared to their mutant counterparts [7]. Additionally, greater lesion size was associated with worse cognition almost exclusively in patients with wild type tumors.…”
Section: Introductionmentioning
confidence: 99%